The Effect Of Audit Rotation, Audit Tenure And Auditor Reputation On Audit Quality With Profitability As Moderating Variable - Mia Austina Anggraini; Sigit Sanjaya; Yamasitha Yamasitha; Yulasmi Yulasmi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Putra Indonesia YPTK, 2022)
This study aims to determine the effect of Audit Tenure, Audit Committee and Auditor Reputation on Audit Quality with Profitability as a Moderation variable. The sample used is a manufacturing company listed on the Indonesia Stock Exchange (BEI) 2015-2019. In determining the sample using purposive sampling method.The data used are secondary data and the method of analysis used is logistic regression analysis.The results showed that partially Audit Rotation has a positive and significant effect on Audit Quality with a significant value of 0,012. Partially the Audit Tenure has a positive and insignificant effect on Audit Quality with a significant value of 0,346. Partially Auditor Reputation has a positive and significant effect on Audit Quality with a significant value of 0,028. Partially Audit Rotation has a positive and significant effect on Audit Quality with Profitability as a moderating variable with a insignificant value of 0,655. Partially the Audit Tenure has a positive and significant effect on Audit Quality with Profitability as a moderating variable with a insignificant value of 0,720. Partially, Auditor Reputation has a positive and significant effect on Audit Quality with Profitability as a moderating variable with a significant value of 0,000. Simultaneously the Audit Tenure, Audit Committee and Auditor Reputation have a positive and significant effect on Audit Quality with profitability as a moderating variable with a significant value of 0,003.